2015
DOI: 10.1111/bju.13192
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term response to renal ischaemia in the human kidney after partial nephrectomy: results from a prospective clinical trial

Abstract: Objective To assess the 1-year renal functional changes in patients undergoing partial nephrectomy with intra-operative renal biopsies. Patients and Methods A total of 40 patients with a single renal mass deemed fit for a partial nephrectomy were recruited prospectively between January 2009 and October 2010. We performed renal biopsies of normal renal parenchyma and collected serum markers before, during and after surgically induced renal clamp ischaemia during the partial nephrectomy. We then followed patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Kallingal et al . found that the kidney ischemic changes at the cellular level recovered after reperfusion with no correlation between renal functional at 1 year and WIT …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Kallingal et al . found that the kidney ischemic changes at the cellular level recovered after reperfusion with no correlation between renal functional at 1 year and WIT …”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the impact of long WIT on postoperative renal function is maximized in the setting of a single renal unit . In the presence of two renal functioning units, its impact is present on the short term . Recovery of renal function after PN takes up to 1 year to stabilize, thus evaluating the risk factors affecting early postoperative renal function might be changed on the long‐term .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] A clinical scenario that corresponds well to this form of experimental IR is clamping the renal artery prior to partial nephrectomy as performed in urological oncology to save functioning renal tissue. 18,19,21 However, in patients with a solitary kidney, the incidence of AKI positively correlated with ischaemia duration and was significantly higher than in patients with two functioning kidneys 20 suggesting that in patients with two kidneys, hyperfiltration of the contralateral non-ischaemic kidney masks IR-induced damage of the operated kidney. [18][19][20][21] This led to the suggestion that human kidneys may have a higher IR tolerance than kidneys from small laboratory animals used in experimental IR studies.…”
Section: Clinical Renal Ir Injurymentioning
confidence: 95%
“…IR may be induced bilaterally or unilaterally with or without preceding unilateral nephrectomy. [18][19][20][21] This led to the suggestion that human kidneys may have a higher IR tolerance than kidneys from small laboratory animals used in experimental IR studies. [15][16][17] A clinical scenario that corresponds well to this form of experimental IR is clamping the renal artery prior to partial nephrectomy as performed in urological oncology to save functioning renal tissue.…”
Section: Clinical Renal Ir Injurymentioning
confidence: 99%